2015
DOI: 10.1016/j.ultsonch.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the liquid viscosity on the formation of bubble structures in a 20 kHz field

Abstract: The cavitation field in a cylindrical vessel bottom-insonified by a 19.7kHz large area transducer is studied experimentally. By adding controlled amounts of Poly-Ethylene Glycol (PEG) to water, the viscosity of the liquid is varied between one- and nine-fold the viscosity of pure water. For each liquid, and for various displacement amplitudes of the transducer, the liquid is imaged by a high-speed camera and the acoustic field is measured along the symmetry axis. For low driving amplitudes, only a spherical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…It was found that with an increase in the value of absolute moisture content, the frequency of the sound field increases in a parabolic relationship. This interval of sound frequency is comparable with the studies of many scientists [11][12][13][14][15], in particular the one of Matteo Erriu et al [11], where the effect of ultrasound on microorganisms was examined.…”
Section: Discussionsupporting
confidence: 87%
“…It was found that with an increase in the value of absolute moisture content, the frequency of the sound field increases in a parabolic relationship. This interval of sound frequency is comparable with the studies of many scientists [11][12][13][14][15], in particular the one of Matteo Erriu et al [11], where the effect of ultrasound on microorganisms was examined.…”
Section: Discussionsupporting
confidence: 87%
“…Some bubble paths start from the transducer and converge towards a hemispherical cap, which also attracts bubbles nucleated above. Such structures are commonly found in experimental arrangements where the transducer area is at the same level as a surrounding solid wall [54], and share some similarities with cone bubble structures. It is clearly seen that the bubble paths do not necessarily coincide with the liquid streamlines.…”
Section: Bubble Pathsmentioning
confidence: 77%
“…21) Each liquid sample of 300 ml was contained in a rectangular glass vessel (70 × 70 × 80 mm) with a water jacket to control the temperature at 15 °C. Temperature control is essential in experiments on viscous liquids, because the heating due to viscous dissipation 22) causes the temperature to rise, which results in a decrease in viscosity. Kr gas was filled in the space above the solution to protect air from being dissolved into the solution.…”
Section: Experimental Methodsmentioning
confidence: 99%